1998
DOI: 10.1080/13102818.1998.10818989
|View full text |Cite
|
Sign up to set email alerts
|

Anther Culture Regeneration fromHelianthus Mollis(M-020) and its Hybrid Combinations

Abstract: Anthers from the He/ianthus mollis (M-020) species and from the hybrid combination H.mollis (Jvf-020) x H.annuus and H.annuus x H.mollis (lv/-020) were isolated. Different variants of nutrient media were tested. The most suitable medium for plant regeneration proved to be the B5 medium without hormones and with reduced sucrose content. Regeneration was obtainedji•om the H.mollis (M-020) as well asji•om the hybrid combination H.mollis (M-020) x H.annuus. On~y well formed embryos were obtained from the reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The doubled haploids of sunflower can be produced in vitro from an anther culture by direct embryogenesis [ 9 , 17 , 38 , 39 ], indirect embryogenesis [ 13 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], or indirect shoot organogenesis [ 10 , 17 , 38 , 40 , 44 , 47 , 48 , 49 , 50 , 51 , 52 ] ( Figure 1 ). Several independent research groups have reported the formation of callus tissue from anther culture without any subsequent morphogenic response ( Table 1 and Table 2 ) [ 9 , 17 , 30 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 53 ].…”
Section: Production Of Sunflower Haploids In Isolated Anther Culturesmentioning
confidence: 99%
See 4 more Smart Citations
“…The doubled haploids of sunflower can be produced in vitro from an anther culture by direct embryogenesis [ 9 , 17 , 38 , 39 ], indirect embryogenesis [ 13 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], or indirect shoot organogenesis [ 10 , 17 , 38 , 40 , 44 , 47 , 48 , 49 , 50 , 51 , 52 ] ( Figure 1 ). Several independent research groups have reported the formation of callus tissue from anther culture without any subsequent morphogenic response ( Table 1 and Table 2 ) [ 9 , 17 , 30 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 53 ].…”
Section: Production Of Sunflower Haploids In Isolated Anther Culturesmentioning
confidence: 99%
“…The time interval from the beginning of anther culture to callus tissue formation and the subsequent organogenesis or embryogenesis varies considerably. In particular, callus is formed in vitro on days 5–10, depending on the genotype [ 40 , 42 , 51 ], on days 10–15 [ 45 , 54 ], on days 15–20 [ 14 , 52 ], and after 4 weeks of cultivation [ 41 , 44 ]. Indirect shoot organogenesis or embryogenesis is observable after 4 weeks of culture [ 10 ] and later, after 80–100 days [ 52 ] or 120 days [ 51 ].…”
Section: Production Of Sunflower Haploids In Isolated Anther Culturesmentioning
confidence: 99%
See 3 more Smart Citations